Investigating the impacts of replacing fishmeal with dietary wheat gluten meal on the growth, immunity, and disease resistance of juvenile pearl gentian groupers - Ray Watson Gyan, Dr.; Mpwaga Alatwinusa Yohana; Qihui Yang; Beiping Tan; Shuyan Chi; Yuanming Yi (Aquaculture Reports, 2024)
This research was performed to assess the possibility of substituting fishmeal (FM) with wheat gluten meal (WGM) at different levels. WGM in the total diet (%) are as follows; W0 (0%), W10 (10.21%), W12 (12.42%), W14 (14.65%), W16 (16.87%), and W19 (19.1%) as well as its effects on growth, and immunity in juvenile pearl gentian groupers (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂). A sum of 540 healthy fish (average initial body weight 11.04 ± 0.02 g) was selected randomly and put in eighteen fibreglass tanks (0.3 m3) (six groups with three replicate) at a density of 30 fish per tank and fed with experimental diets twice daily at 08:00 and 16:00 to apparent satiation for eight weeks. WGM102 had a significantly higher weight gain rate (498.82±22.50%) than the control group (345.57±24.93%) (P < 0.05). WGM12 had a lower feed conversion ratio (FCR) (0.87±0.02) than the control group (WGM0) (1.04±0.10). Compared to the control group, WGM14 and WGM106 had higher levels of Acid phosphatase, Lysozyme, and Glutathione Peroxidase in fish than in the control group. The histopathological analyses in fish gut displayed that villus length and villus width depth were statistically different among the treatment groups (P < 0.05) and increased in the WGM12 than the control group (WGM0). The relative abundance for Bacillus and Photobacterium was abundant fish fed WGM12 and WGM14 compared to the control group WGM0 at the genus level. Fish fed the control diet had higher cumulative mortality (69%) than those fed the WGM12 (38%) after the bacteria challenge test within 14 days (P < 0.05). In summary, concerning all the parameters, replacing FM with WGM at 12.42% may cater to all the dietary nutritional requirements for fish.